Additives Incorporated in Cellulose Acetate Membranes to Improve Its Performance as a Barrier in Periodontal Treatment - Fornazier, Mariana; Gontijo de Melo, Patricia; Pasquini, Daniel; Otaguro, Harumi; Pompêu, Gabriela Ciribelli Santos; Ruggiero, Reinaldo (Frontiers in Dental Medicine, 2021)
In this study, we prepared cellulose acetate membranes, by means of casting mold, incorporated with two additives, sodium carboxymethyl lignin and calcium glycerophosphate, in order to improve properties for periodontal applications. The membranes were characterized from the morphological, structural, thermal and mechanical point of view, as well as by physiological pH tests. The results showed that membranes with additives improve the physical-chemical and mechanical properties, especially when the two additives are present in the same membrane, which can be attributed to the important synergy between them. The most significant effects occur in increasing the thickness and decreasing the density, which reflects in the porosity of the membranes, although the added amounts do not exceed 1.4%. A 1% increase in lignin concentration does not change the thickness and density of the membrane, but that amount of lignin plus 0.4% calcium glycerophosphate increases the thickness of the membrane by 42% and decreases the density by about 6%. Although there is a decrease in mechanical properties, as observed in Young's modulus and crystallinity, the significant and intermittent increase in sample weight loss with both additives in physiological solution indicates that, in the long run, it can be used as a degradable barrier.